Analysis of the availability of medicines for the treatment of servicemen with injury and wound of the brain - О. P. Shmatenko; G. V. Osedlo; O. M. Vlasenko; O. V. Pleshkova (The State Expert Center of the Ministry of Health of Ukraine, 2019)
The most important areas that determine the effectiveness of the medical support system at all stages of providing medical assistance to servicemen is the rational use and availability of medicines and pharmaceutical assistance in general. Under the influence of the situation in eastern Ukraine, the instability of the market economy, the existing budget deficit for the military medical service, the availability of certain groups of drugs is of particular relevance, which fully applies to drugs for the pharmacotherapy of injuries and brain injuries. The purpose of the study is to analyze the availability of medicines for pharmacotherapy of injuries and wounds of the brain. In conducting the study, the following methods of analysis were used: system-review, bibliographic and marketing. Analysis of scientific literature data showed that for pharmacotherapy of craniocerebral wounds and injuries such groups of drugs as psychoanaleptics (N06), blood substitutes and perfusion solutions (B05), peripheral vasodilators (C04), calcium antagonists (C08), analgesics (N02) are used. and psycholeptic drugs (N05), etc., which counted 1 300 trade names of drugs. The analysis of the pharmaceutical market in recent years has allowed us to single out three main factors (index) affecting the growth of expenditures on drug provision for servicemen, the replacement index; inflation index; innovation index Analyzing the availability of drugs by price proposals, it was found that the number of inaccessible drugs decreased within five years by more than 30% and amounts to 7.93% or 103 drugs from the total range of drugs for medical support of servicemen with injury and wound of the brain. That is why it is advisable to conclude that the replacement index has almost no effect on reducing the level of drug costs for servicemen/ In the study of the inflation index, it was found that the pricing of domestic drugs depends on the level of inflation, the cost of foreign-made drugs is in direct proportion to the growth of the dollar. Analysis of the innovation index of the domestic drug market for medical support of servicemen with injury and wound of the brain showed that only 77 original drugs are used for pharmacotherapy, which is 5.92% of the total number of drugs.